PENGARUH KEPEMIMPINAN, MOTIVASI DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN HOTEL DAN RESTO ALAM INDAH - Sesanti Handayani, 07.05.51.0080; Wanuri, Wanuri (Students Journal of Economic and Management, 2012)
This study examined the effect of interest of leadership, motivation and morale of the employees performance Alam Indah Hotel and Restaurant Population of this study were employees of Alam Indah Hotel and restaurant totaling 102 people. Sampling was done by the method in which the population census as a sample, and obtained 101 respondents. Methods of data analysis is multiple linear regression. Is a multiple linear regression analysis used to determine the effect of two or more independent variables on a dependent variable. The conclusion of this study are as follows: (1) leadership had no effect on performance. (2) motivation has a positive effect on performance. (3) Morale positive effect on performance.Key words: performance, leadership, motivation and morale